Impact of Digital Learning Tools on Student Performance in Kenya - Mwangi, Julius (African Journal of Education and Practice, 2024)
Purpose: The aim of the study was to investigate the impact of digital learning tools on student performance in Kenya. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: Digital learning tools in Kenya enhance student engagement by offering interactive and accessible educational content. These tools enable personalized learning, allowing students to progress at their own pace. However, challenges like inconsistent internet access and limited digital literacy among teachers can hinder effectiveness. Despite these obstacles, the adoption of digital technologies has positively impacted student performance in Kenya. Unique Contribution to Theory, Practice and Policy: Technology acceptance model (TAM), constructivist learning theory & media richness theory may be used to anchor future studies on the impact of digital learning tools on student performance in Kenya. Educational tools should be specifically tailored to align with Kenya's national curriculum. Develop national policies that promote the equitable distribution of digital learning tools across different regions, including rural areas.